Oxidants, antioxidant nutrients and the athlete - Packer, L. (Journal of Sports Sciences, 1997)
Strenuous physical exercise induces oxidative stress. There may be a number of sources of this oxidative stress, including mitochondrial superoxide production, ischaemia-reperfusion mechanisms and auto-oxidation of catecholamines. Severe or prolonged exercise can overwhelm antioxidant defences, which include vitamins E and C and thiol antioxidants, which are interlinked in an antioxidant network, as well as antioxidant enzymes. Evidence for oxidative stress and damage during exercise comes from direct measurement of free radicals, from measurement of damage to lipids and DNA, and from measurement of antioxidant redox status, especially glutathione. There is little evidence that antioxidant supplementation can improve performance, but a large body of work suggests that bolstering antioxidant defences may ameliorate exercise-induced damage, suggesting that the benefits of antioxidant intervention may be for the long term rather than the short term.